2016
DOI: 10.3233/blc-160075
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Biomarkers in Bladder Cancer

Abstract: Bladder cancer is a molecularly heterogeneous disease characterized by multiple unmet needs in the realm of diagnosis, clinical staging, monitoring and therapy. There is an urgent need to develop precision medicine for advanced urothelial carcinoma. Given the difficulty of serial analyses of metastatic tumor tissue to identify resistance and new therapeutic targets, development of non-invasive monitoring using circulating molecular biomarkers is critically important. Although the development of circulating bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 97 publications
0
26
0
Order By: Relevance
“…27,28 Until now, a plethora of single molecular biomarkers have been reported, [7][8][9] but only a few have been validated for clinical use or recommended by guidelines. [29][30][31] On the other hand, the predictive effect of a multiple gene signature has been highlighted. 32,33 In this study, we conducted GSVA to screen the most important Recent studies have revealed the involvement of EMT in the pathogenesis of cancers, including BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Until now, a plethora of single molecular biomarkers have been reported, [7][8][9] but only a few have been validated for clinical use or recommended by guidelines. [29][30][31] On the other hand, the predictive effect of a multiple gene signature has been highlighted. 32,33 In this study, we conducted GSVA to screen the most important Recent studies have revealed the involvement of EMT in the pathogenesis of cancers, including BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating nucleic acids are currently being evaluated as biomarkers in several different diseases (210,211,212,213,214,215). One of the criteria for biomarkers in clinical use is high sensitivity and specificity, e.g.…”
Section: Tissue Injury and Release Of Nucleic Acidsmentioning
confidence: 99%
“…Circulation biomarkers can facilitate the screening of cancer, understanding of tumor biology, and early discovery of recurrence with minimum invasion. (5) The study of circulating biomarkers is of great concern due to the identification of more and more serum molecules, such as proteins, metabolites, and microRNAs recently. (6) Liquid chromatography-mass spectrometry (LC-MS)-based metabolomics is a powerful tool that has been used to discover novel circulating biomarkers for many diseases.…”
mentioning
confidence: 99%